Identification and expression assay of calcium-dependent protein kinase family genes in Hevea brasiliensis and determination of HbCDPK5 functions in disease resistance. (22nd November 2021) - Zhang, Bei; Song, Yufeng; Zhang, Xiaodong; Wang, Qiannan; Li, Xiuqiong; He, Chaozu; Luo, Hongli
Abstract: Calcium (Ca 2+ ) signaling is one of the earliest factors to coordinate plant adaptive responses. As direct sensors and activators of Ca 2+ signals, calcium-dependent protein kinases (CDPKs) were reported to be widely involved in regulating different biotic and abiotic stress stimuli. In this study, 32 Hevea brasiliensis CDPK ( HbCDPK ) genes were predicted and classified into four subgroups. Among them, the full-length coding sequences of 28 HbCDPK genes were confirmed by RT-PCR and verified by sequencing. Putative cis-elements assay in the promoters of HbCDPKs showed that most of the HbCDPK genes contained gibberellic acid-responsive element (GARE), abscisic acid-responsive element (ABRE), salicylic acid-responsive element (SARE), defense and stress responsive element (TC-rich repeats) and low-temperature response element (LTR), which could be activated by different biotic and abiotic stresses. Real-time PCR analysis indicated that 28 HbCDPK genes respond to infection of pathogenic fungi and a variety of phytohormones. Subcellular localization was observed with most HbCDPKs located in cell membrane, cytoplasm or organelles. Some HbCDPKs were confirmed to cause reactive oxygen species (ROS) production and accumulation in rubber tree mesophyll protoplast directly. HbCDPK 5 was strongly induced by the inoculation with Colletotrichum gloeosporioides and was chosen for further analysis. HbCDPK5 localized to the cell membrane and cytoplasm, and obviously regulated the accumulation of ROS in rubber tree mesophyll protoplast. Overexpression of HbCDPK5 in Arabidopsis enhanced the resistance to Botrytis cinerea . These results indicate that rubber tree CDPK genes play important roles in plant disease resistance.